Өзбекстанда аўыл хожалығын басқарыўды жәҳән стандартына алып шығыў басқышлары (ILIM hám JÁMIYET, 2020)
This article shows the implementation of the cluster method in the agricultural sector. The article analyzes the growth of agricultural production.